2021
DOI: 10.21037/tcr-20-3341
|View full text |Cite
|
Sign up to set email alerts
|

Telomere in colorectal cancer associated with distant metastases and predicted a poor prognosis

Abstract: Background: Telomere is essential for chromosomal stability and its length has been proven to be related to prognosis in many malignant tumors. This study aims to investigate the relevance of telomere length with clinical and pathologic features and its prognostic value in colorectal cancer (CRC).Methods: Telomere status of CRC and adenoma cells were measured by telomere-specific quantitative fluorescent in situ hybridization (Q-FISH). The relative telomere length (RTL) was calculated as the mean telomere fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We confirmed that primary CRC tissue exhibits shorter TL compared to non-cancerous reference mucosa, which has been previously described by us and many other studies 13 , 17 , 22 26 . This phenomenon strongly supports the notion that the telomere crisis might be one of the pivotal events in the disease development 24 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We confirmed that primary CRC tissue exhibits shorter TL compared to non-cancerous reference mucosa, which has been previously described by us and many other studies 13 , 17 , 22 26 . This phenomenon strongly supports the notion that the telomere crisis might be one of the pivotal events in the disease development 24 .…”
Section: Discussionsupporting
confidence: 92%
“…Our result is in agreement with Le Balc’h et al who also did not find any association between TL in tumours of patients with CRC and the presence or absence of distant metastasis at the time of diagnosis 17 . However, in a study by Ye et al patients diagnosed with advanced CRC with distant metastases had shorter telomeres in primary tumours compared to those of non-metastatic patients 22 .…”
Section: Discussionmentioning
confidence: 90%
“…Clinically, there has been much interest in telomere length and telomerase activity and its association with malignant transformation (90,91). Several studies indicated that CRCs display shorter telomeres when compared with the surrounding mucosa, especially in distant metastases (92)(93)(94). Telomere shortening can be accelerated by oxidative stress due to 8-oxoguanine formation at telomeres (95,96).…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length in cancer tissue was substantially shorter than in normal mucosa. Advanced CRC (stage II-IV) cancers have longer telomeres than stage I tumors (Ye et al, 2021). According to Taheri et al (2022), CRC tissue had reduced hTERT expression levels.…”
Section: Telomerasementioning
confidence: 99%